Dietary polyphenols as modulators of cell signaling and inflammation in colorectal carcinogenesis - Tan, Bee Ling; Zulkifli, Fatimah; Norhaizan, Mohd Esa (Frontiers in Nutrition, 2025)
Colorectal cancer is the second leading cause of cancer mortality worldwide. Although current chemopreventive drugs can suppress the proliferation of cancer cells, their use is often limited by adverse side effects, including toxicity, development of resistance, and lack of selectivity. The main side effects associated with continuous infusion of 5-fluorouracil (5-FU) are mucositis, vomiting, nausea, and diarrhea. Dietary factors play a critical role in colorectal cancer management and have gained attention as alternative strategies for cancer prevention. Evidence from preclinical and human studies suggests that polyphenols exert anti-colon cancer activity. However, the mechanisms underlying these effects remain poorly understood. This review highlights the potential of polyphenol-rich foods in the prevention of colorectal cancer, particularly regarding molecular aspects that may provide a plausible means for the prevention of colorectal cancer. Overall, elucidating the role of polyphenols in redox regulation of inflammation may offer useful strategies for intervention and contribute to colorectal cancer prevention.